Pengaturan Hukum Hak Atas Tanah dalam Perkawinan Campuran Menurut Undang-undang Pokok Agraria - Zahra Maulida Aulia; Gunawan Djajaputra (UNES Law Review, 2024)
Mixed marriage is a marriage that occurs between an Indonesian citizen and a foreign citizen. Mixed marriages without a marriage agreement create a mix of assets, the mix of assets in the form of land can have an impact on the assets of each party, as then according to Law number 5 of 1960 concerning Agrarian Regulations that a citizen Foreigners cannot obtain/own land ownership, either through a will or by mixing assets due to marriage. The research method used in this writing is a juridical-normative research method, using a type of literature study with a statutory approach and a case approach. Regarding a mixed marriage that occurs and there is no separation of assets which causes the foreign citizen to indirectly violate the Agrarian Law Article 21 paragraph (3).